Home Learning in Timesof Covid: Parents’Experiences, Dificultiesand Coping Strategies - DE RAMOS, JOEY (International Journal of Arts, Sciences and Education, 2022)
ABSTRACT PURPOSE. The purpose of this research study was to explore the parents’ experiences of home learning in times of COVID-19 their difficulties and their coping strategies. RESEARCH PROBLEM. How does parents overcome the difficulties experienced on home learning in times of covid 19? METHODOLOGY. A descriptive qualitative study was planned to explore the challenges of parents about home learning and management during COVID-19 to get an insight into real-life experiences regarding their difficulties and their coping strategies. CONCLUSIONS. Based from the findings of the study, the researcher concluded the following: 1. Home learning foster difficulties in this pandemic time such as retrieval and distribution process of the learning packages, simultaneous roles at home, education and work and health related restrictions. 2. For the strategies encountered in modular distance learning includes the proper time management, constant communication with the adviser regarding the distribution and retrieval of the learning packages and lessons which are very hard to understand and the attitude towards the new normal learning. SIGNIFICANCE. This action research was conducted to help teachers and school administrators to adjust their plans regarding home learning in collaboration with parents. Keywords: COVID-19, home learning, modular distance learning, parents’ difficulties